Visual Perspectives on Majority-World Adolescent Thriving - Catherine Ann Cameron (2018)
This paper offers socio-ecological, situated perspectives on adolescent resilience derived from an application of interpretive visual methodologies to deepen understanding of adaptive youth development in diverse majority-world cultural contexts (South Africa, Thailand, China, Mexican migration to Canada). The research is not "cross-cultural"; by contrast, it situates youth engagement contextually, using local perspectives, especially perspectives of adolescents themselves, on "growing up well" under adverse circumstances, to interrogate conceptions of resilience in cultural context. Participants are viewed as members of cultural communities: observations with a small number of individuals are not generalized to national groups. Rather, knowledge gained by these methods is employed to enrich knowledge of the processes of majority-world youth thriving despite such adversities as poverty and social displacement. © 2013 The Authors. Journal of Research on Adolescence © 2013 Society for Research on Adolescence.